A multi-objective framework for distributed energy resources planning and storage management - CEYLAN, OĞUZHAN (My University, 2022)
The use of energy storage systems (ESS) and distributed generators (DGs) to improve reliability is one of the solutions that has received much attention from researchers today. In this study, we utilize a multi-objective optimization method for optimal planning of distributed generators in electric distribution networks from the perspective of multi-objective optimization. The objective is to improve the reliability of the network while reducing the annual cost and network losses. A modified version of the multi-objective sine-cosine algorithm is used to determine the optimal size, location, and type of DGs and the optimal capacity, location, and operation strategy of the ESS. Three case studies of IEEE 33-bus, 69-bus and 141-bus test systems with Turkish DG and load data were conducted to validate the effectiveness of the proposed approach. The distribution of the Pareto front solutions and the optimal objective functions are compared with the other known algorithms. The simulation results show that the average energy not supplied and annual energy losses for the test systems are reduced by up to 68% and 64%, respectively. Moreover, the Pareto fronts of the proposed method show a better distribution and dominate those obtained by MOGWO, MOSMA, NSGA-II, MOPSO and MOEA-D according to three different Pareto optimization metrics. Finally, the computational effort result shows faster convergence of MOSCA compared to MOGWO, MOSMA, NSGA-II, MOPSO and MOEAD.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Chemical Engineering and Technology; Engineering and Technology; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MÜHENDİSLİK, KİMYASAL; ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); ENGINEERING, CHEMICAL; Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Genel Mühendislik; Kimyasal Sağlık ve Güvenlik; Akışkan Akışı ve Transfer İşlemleri; Genel Enerji; Kimya Mühendisliği (çeşitli); Mühendislik (çeşitli); Genel Kimya Mühendisliği; Kolloid ve Yüzey Kimyası; Kataliz; Yakıt Teknolojisi; Enerji (çeşitli); Fizik Bilimleri; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; General Engineering; Chemical Health and Safety; Fluid Flow and Transfer Processes; General Energy; Chemical Engineering (miscellaneous); Engineering (miscellaneous); General Chemical Engineering; Colloid and Surface Chemistry; Catalysis; Fuel Technology; Energy (miscellaneous); Physical Sciences; Distributed energy sources; Heuristic algorithms; Multi-objective optimization; Power system planning; Reliability; Network losses; RADIAL-DISTRIBUTION SYSTEM; OPTIMAL PLACEMENT; RELIABILITY; CAPACITORS; REANALYSIS; Distributed energy sources; Heuristic algorithms; Multi-objective optimization; Power system planning; Reliability; Network losses